Managing Teaching Practice for Quality Assurance in Teachers Production in Tertiary Institutions in Rivers State - Odunlade , Powell Kehinde (International Journal of Educational Management, 2022)
The study focused on managing teaching practice for quality assurance in tertiary institutions in Rivers State. Two research questions and two hypotheses were answered and tested respectively in the study. The design of the study was descriptive survey design while the population of the study consisted of four tertiary institutions offering teacher education programmes in the state. The population of respondents comprised 5,978 students and 802 supervisors thus, giving a total of 6,780 respondents. The sample size of 475 respondents, comprising 385 students and 90 supervisors was drawn from the population of the study through Taro Yamane sample determination technique using disproportionate sampling technique. The instruments used for data collection was the questionnaire titled “Questionnaire for Managing Teaching Practice for Quality Assurance in Teachers Production in Tertiary Institutions in Rivers State (QMTPQATPTIRS)”. The questionnaire items were responded to on a four point modified Likert scale. The face and content validity were determined by experts while the reliability of the questionnaire was determined using Cronbach Alpha with reliability index of 0.72. The research questions were answered using mean while the hypotheses were tested using z-test statistic. The findings of the study revealed that co-operating school teachers did not have any input in the grading of student-teachers they mentored which in turn had informed their indifference to teaching practice. The study further revealed that student-teachers were ill-motivated by what they see of the teaching profession in Nigeria which had contributed to the unserious attitude of some of them. The study therefore concluded that teaching practice exercise was not well carried out in the state and such recommended that Teacher training institutions should incorporate at least fifty percent (50%) inputs from co-operating teachers in their teaching practice assessment score sheet. This is to make difficult for faculty supervisors to sideline them.